2010
DOI: 10.1242/dev.054791
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-dependent transdifferentiation of pancreatic progenitor cells into hepatocytes is dependent on transient suppression of WNT signalling

Abstract: SummaryDevelopmentally, the pancreas and liver are closely related and pathological conditions -including elevated glucocorticoid levelsresult in the appearance of hepatocytes in the pancreas. The role of the WNT signalling pathway in this process has been examined in the model transdifferentiating pancreatic acinar AR42J-B-13 (B-13) cell. Glucocorticoid treatment resulted in a transient loss of constitutive WNT3a expression, phosphorylation and depletion of -catenin, loss of -catenin nuclear localisation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…siRNA-mediated knockdown of SGK1 and overexpression of SGK1 inhibited and promoted (without the requirement for glucocorticoid) transdifferentiation, respectively, unequivocally demonstrating a regulatory role for SGK1 in the response. Our data also suggest that the mechanism is likely to involve crosstalk with the WNT signalling pathway, which has previously been shown to regulate B-13 cell transdifferentiation (Wallace et al, 2010c), because overexpression of SGK1 inhibited transcriptional activity of distal WNT signalling, an effect that was absent when the SGK1 kinase function was blocked. The transdifferentiation of pancreatic acinar cells to hepatocyte-like…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…siRNA-mediated knockdown of SGK1 and overexpression of SGK1 inhibited and promoted (without the requirement for glucocorticoid) transdifferentiation, respectively, unequivocally demonstrating a regulatory role for SGK1 in the response. Our data also suggest that the mechanism is likely to involve crosstalk with the WNT signalling pathway, which has previously been shown to regulate B-13 cell transdifferentiation (Wallace et al, 2010c), because overexpression of SGK1 inhibited transcriptional activity of distal WNT signalling, an effect that was absent when the SGK1 kinase function was blocked. The transdifferentiation of pancreatic acinar cells to hepatocyte-like…”
Section: Discussionsupporting
confidence: 64%
“…Previous work has demonstrated that -catenin phosphorylation, which targets the protein for degradation (Hoppler and Kavanagh, 2007), and reductions in the levels of -catenin are early upstream 409 Role for SGK1 in transdifferentiation events to C/EBP- induction and B-13 transdifferentiation to B-13/H cells (Wallace et al, 2010c). It was therefore hypothesised that expression of SGK1C and SGK1F or induction of endogenous SGK1C resulted in phosphorylation of -catenin.…”
Section: Sgk1c and Sgk1f Phosphorylate -Cateninmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticoid dexamethasone could efficiently induce rat pancreatic exocrine cells into hepatocytes [13]. Similarly, another report confirmed the inductive role of dexamethasone in transdifferentiation of pancreatic acinar cells into functional hepatocytes through a transient suppression of Wnt signaling [14]. These findings may suggest that adult pancreatic cells might retain epigenetic memory from their common embryonic origin with hepatocytes and thereby are flexible to convert into hepatocytes under permissive conditions.…”
Section: Induced Pluripotent Stem Cells (Ip-mentioning
confidence: 67%